Movement Aware Smart Street-lights for Efficient Energy Utilisation: Movement Aware Smart Street-lights for Efficient Energy Utilisation - Khan, Muhammad Sohail; Qadeem, Abdul; Ali, Faiz; Naeem, Bushra; Shabbir, Bilal; Ali, Raza; Shoaib, Muhammad Ali (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Now a days, energy is an essential resource as the number of energy resources are sinking day by day. Movement Aware Smart Street light is a simple yet powerful concept, which uses transistor as a switch and replaces the manual system. It instantly switches the lights ON when the sunlight goes below the visible region. As energy is the scarcest source, this requires finding innovative ways to use it efficiently. Big cities consume a large amount of electricity and it is required to save energy by operating the street-lights at the time of need. In this paper, an effective method of street-light operation is presented which detects the sun set and sun rise alongside detection of vehicle movement on roads to utilise the energy only when it is required. Furthermore, a system is proposed which reduces energy consumption by replacing manually operated street-lights as they are not switched OFF even the sunlight appears and also switched ON earlier before sunset. The proposed mehtod has saved the municipal utility budget by 35% - 45% through energy saving. This paper also discussed the elimination of manual operation like ON time and OFF time setting and clearly demonstrates the working of transistor in saturation region and cut-off region.